Scott, Foresman beginning dictionary - Thorndike, Edward L. (Edward Lee) 1874-1949; Barnhart, Clarence Lewis 1900- (Scott, Foresman, 1976)
A beginning dictionary including illustrations and examples of usage in the definitions and exercises and lessons teaching use of a dictionary.